Farmers’ Appraisal of the Selected Financial Schemes for Rural Development by National Bank for Agriculture and Rural Development (NABARD), Shimla District, Himachal Pradesh - Chauhan, Aditi; Mehta, Piyush; Raina, Krishan Kumar (International Journal of Economic Plants, 2017)
Financial requirement of agriculture is a great necessity of agricultural financing with a view of satisfying the various operational needs of the farmers. Different financial schemes are developed by the NABARD (National Bank for Agriculture and Rural Development) for the rural development and for the farmers of allied sectors in rural areas. These financial schemes need to be improved and revised so that the faming beneficiaries can accumulate maximum profits from these financial schemes. Farmer’s appraisal helps in valuation of these schemes and helps in restructuring the policies or financial requirement of the farmers so that the farming beneficiaries can make out maximum profit from these schemes. Though many studies have been undertaken on the various schemes provided by the NABARD but very few have touched on the farmer’s appraisal. This study has addressed issues like how these schemes are proving to be beneficial to the rural India and it has also attempted to critically analyze the financial support to the farming community at large. The study has also observed the need for improvisation in such financial schemes through the suggestions and feedbacks of farming beneficiaries as well.